Polymerisation catalysts enabling carbon dioxide utilization - Lindeboom, W (2023)
This thesis describes the development of homogeneous catalysts for epoxide/carbon dioxide (CO2) ring-opening copolymerisation (ROCOP). The objective is to increase understanding of the polymerisation mechanism and factors controlling catalyst performance. It ends with an application of the best catalyst to polymerisation of epoxide, carbon dioxide and lactide using ‘switch’ catalysis.